The Formulation of a Special Minimum Criminal Threat System Formulation in the Corruption Law - Doni Cakra Gumilar; Sri Endah Wahyuningsih; Jawade Hafidz (Law Development Journal, 2023)
This study aims to find out how the policy for formulating a special minimum penalty system in the current Corruption Crime Law, what are the weaknesses of the policy for formulating a special minimum penalty system in the current Corruption Law and how is the policy for formulating a special minimum penalty system in the Criminal Act Future corruption. The research method used is normative juridical. Based on the research, it was concluded that the formulation policy of a special minimum penalty system in the Corruption Crime Act is currently seen as having weaknesses, including, the formulation of a special minimum sentence that is too light is seen as having hurt the sense of justice in society and there is no sentencing guideline in the Act. Current Corruption Crimes. In order to overcome the weaknesses in the formulation of a system of special minimum criminal threats in the Corruption Crime Law in the future. This can be solved by revising the policy formulation of a special minimum penalty system by increasing the minimum penalty and including specific minimum criminal penalties in the Corruption Law.